Agent of change : my life fighting terrorists, spies, and institutional racism - Mukbil, Huda (Montreal ; Kingston ; London ; Chicago : McGill-Queen's University Press, 2023)
"In Agent of Change, Huda Mukbil, a Black Arab-Canadian Muslim, chronicles her life as an intelligence officer in Canada's lead spy agency, the Canadian Security Intelligence Service. Mukbil was at forefront of the fight against terrorism after 9/11, and the first such woman to join CSIS. Her mastery of five languages, to say nothing of her subject position, quickly made her a counterrorism expert and a unique and valuable contributor to the organization. She provides a riveting account of her struggle for belonging and acceptance in an agency dominated by former RCMP and police officers, and her confrontation of the new international terrorist threat. In July 2005, she was given a chance to prove her worth when she was called upon by the British Security Service, MI5, to contribute, at the highest level, to its investigations of the terrorist attacks in London. Dazzlingly written, her is an eye-opener for anyone wanting to understand how racism, misogyny, and Islamophobia undermine not only individuals, but institutions and the national interest."--
Cover -- AGENT OF CHANGE -- Title -- Copyright -- Dedication -- Contents -- Abbreviations -- Prologue -- 1 Exile -- 2 A Thousand Minarets -- 3 Remembrance Day -- 4 Rebel Girl -- 5 The Pitch -- 6 Recruitment -- 7 Raison d'être -- 8 Officer in Training -- 9 Sunni Islamic Extremism -- 10 First through the Door -- 11 Operation Crevice -- 12 Loyalty -- 13 London -- 14 The Canadian Spy -- 15 Toronto Region -- 16 Marital Status -- 17 Common Ground -- 18 Official Complaints and Repercussions -- 19 Lean In -- 20 Security Screening -- 21 Fight-or-Flight -- 22 Don't Be a Martyr -- Afterword
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Mukbil, Huda; Canadian Security Intelligence Service -- Officials and employees -- Biography; Canadian Security Intelligence Service; Intelligence officers -- Canada -- Biography; Muslims, Black -- Canada -- Biography; Race discrimination -- Canada; Terrorism -- Prevention; Officiers de renseignements -- Canada -- Biographies; Musulmans noirs -- Canada -- Biographies; Discrimination raciale -- Canada; Terrorisme -- Prévention.; POLITICAL SCIENCE / Security (National & International); Employees; Intelligence officers; Muslims, Black; Race discrimination; Terrorism -- Prevention; Canada; Canadian; Intelligence; Royal Canadian Mounted Police; Security; Service; citizenship; counterintelligence; counterterrorism; culture; espionage; islamophobia; loyalty; operations; police; race; surveillance; terror; war; women; Electronic books; autobiographies (literary works); Autobiographies; Biographies; Autobiographies; Autobiographies